THE ROLE OF THERAPEUTIC ALLIANCE IN SUBSTANCE USE DISORDER TREATMENT FOR YOUNG ADULTS - Urbanoski, Karen A. (2012)
The therapeutic alliance is deemed to be integral to psychotherapeutic interventions, yet little is known about the nature of its role in treatment for substance use disorders (SUD), especially among young people. We investigated baseline predictors of the therapeutic alliance measured mid-treatment, and tested whether the alliance influenced during-treatment changes in key process variables (psychological distress, motivation, self-efficacy, coping skills, and commitment to AA/NA) independent of these baseline influences. Young adults in residential treatment (N=303; age 18-24) were assessed at intake, mid-treatment, and discharge. Older age and higher baseline levels of motivation, self-efficacy, coping skills, and commitment to AA/NA predicted a stronger alliance. Independent of these influences, participants who developed a stronger alliance achieved greater reductions in distress during treatment. Findings clarify a role for alliance in promoting during-treatment changes through reducing distress.